Relevance of micrometastases detected by reverse transcriptase-polymerase chain reaction for melanoma recurrence: systematic review and meta-analysis - Silva, Allisson Monteiro da; Oliveira Filho, Renato Santos de; Ferreira, Lydia Masako; Saconato, Humberto (São Paulo Medical Journal, 2003)
CONTEXT: Cutaneous melanoma presents significant morbidity and mortality. Nowadays, about 90% of them are diagnosed by clinical examination and most are localized melanomas. Sentinel node biopsy has brought about a new and interesting approach towards localized cutaneous melanoma. The meaning of micrometastases in sentinel nodes diagnosed by the reverse transcriptase-polymerase chain reaction is not well established. OBJECTIVE: To define the real value of micrometastases diagnosed by the reverse transcriptase-polymerase chain reaction in relation to melanoma recurrence. METHODS: Systematic literature review and meta-analysis. The Cochrane Library, Medline, Embase and Lilacs were the databases searched. We used the following key words: sentinel node and melanoma; sentinel node and reverse transcriptase-polymerase chain reaction; melanoma and reverse transcriptase-polymerase chain reaction. Cohort studies enrolling localized cutaneous melanoma patients who underwent sentinel node biopsy were selected. Sentinel node evaluations included hematoxylin and eosin, immunohistochemistry and reverse transcriptase-polymerase chain reaction. RESULTS: Out of the 1,542 studies evaluated, four were eligible. The four studies, when combined, were statistically homogeneous. The sample totaled 450 patients grouped as follows: 163 with a sentinel node negative to hematoxylin eosin and immunohistochemistry and positive to the reverse transcriptase-polymerase chain reaction; 192 with a sentinel node negative to hematoxylin eosin, immunohistochemistry and the reverse transcriptase-polymerase chain reaction and 95 patients with a sentinel node positive to hematoxylin eosin and/ or immunohistochemistry. We analyzed the first two groups. The meta-analysis for the random model showed an increased effect from a positive reverse transcriptase-polymerase chain reaction on the recurrence rate. A similar result occurred in the meta-analysis for the fixed effect model. CONCLUSION: Patients with a positive reverse transcriptase-polymerase chain reaction had a greater recurrence rate than those with a negative reverse transcriptase-polymerase chain reaction. This suggests an important role for the reverse transcriptase-polymerase chain reaction in sentinel node examinations. In view of the small sample, a clinical trial could better evaluate this question.